Problematika Pembelajaran Dalam Jaringan (Daring) di RA Rahmat Islamiyah (Studi Kasus Penerapan Metode, Media, dan Evaluasi Pembelajaran) - Sahyan Sahyan; Eka Sasmita Siregar; Heni Fitriani; Rani Andani (AUD Cendekia, 2021)
This study aims to analyze a variety of learning problems in the network (online) both in terms of learning methods, learning media, and learning evaluation. This research was conducted in early childhood at RA Rahmat Islamiyah. This research uses qualitative research methods, based on case studies. The results of the study show that the problems of online learning in terms of learning methods include varied learning methods, limited by time, cannot be observed directly by the teacher, have a tendency to assignment, limit student development achievements, are limited by network constraints. Problems of online learning in terms of learning media, including learning media cannot be varied, have a tendency to audio-visual, often do not make students interactive, vulnerable to high costs, vulnerable to network disturbances. The problems of online learning in terms of learning evaluation include online learning evaluations that cannot assess all aspects, and are vulnerable to fraud